Rancang Bangun Modul Pembangkit Listrik Tenaga Surya (PLTS) Sistem Off-grid Sebagai Alat Penunjang Praktikum Di Laboratorium - Muhammad Syahwil; Nasrudin Kadir (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
This study aims to design and manufacture a practical module for a small-scale off-grid solar power system with a power capacity of 320Wp. This module consists of the main components of an off-grid type solar power system such as solar panels, Solar Charger Controller (SCC), batteries, inverters, ac/dc loads and power meter measuring instruments integrated in one module. The method used is laboratory research methods and literature study. The literature study method is to look for literature related to solar power plant as a support in making modules and laboratory methods, namely testing modules/ systems with certain conditions. Stages This research method includes identification of problems in the laboratory, literature study, design/layout of the PLTS module, determining the type and analysis of the capacity of solar panels, SCC, inverters and batteries, supplying materials/components, manufacturing modules, and testing modules in the laboratory. The output and benefits of this research are getting a practical module for the solar power plant system which makes it easier for students to understand the working principles of the PLTS system; also to optimize practicum activities in the laboratory. From the results of testing, measurement, and data analysis that have been carried out by the off-grid solar power plant (PLTS) module that has been made to function properly and works in accordance with the principle of the off-grid PLTS system, generating electricity according to the capacity of the solar panel, The solar charge controller works in accordance with its function to regulate charge and discharge of battery storage and the inverter is able to serve the load according to its capacity so that this module is ready to be used as a practical module in learning activities in the laboratory.